도·농 균형사회 실현을 위한 선진 각국의 정책기법 연구 - 마상진 (한국농촌경제연구원, 2006)
The purpose of this study was to investigate how to introduce policy proofing system ― rural impact assessment for balanced development between urban and rural area in Korea. For the purpose, literature on impact assessment research was reviewed in terms of concept, process, principle, and scope: domestic cases of impact assessment were analysed including impact assessment including environment impact assessment, regulatory impact analysis, balanced development impact assessment, pre-validity analysis, policy quality management, gender impact assessment, and technology impact assessment; foreign cases of rural impact assessment such as Rural Proofing of UK, Rural Lens of Canada, and Rural Area Flexibility Analysis of USA New York state were analysed. As a result of above reviews and analyses with help of expert advices, this study suggested the following ideas about policy proofing system for balanced development between city and rural area: ① Rural impact assessment is to improve the lives of rural residents by checking the impact of government's initiatives in rural area in the process of policy design, development, implementation and evaluation. ② Rurality should be considered including poor infrastructure, stagnant rural economy, declining rural society and conserving environment and multi-functionality. ③ Steering body should be established for research and development; data and information collecting; recommendation and education; coordination and consulting; and promotion and publication. In addition ④ some operational tasks for system settlement should be implemented including rule making for rural impact assessment; building up expert group to support and consult this system; developing rural impact checklist for policy makers; producing rural statistics and rural index; education of policy makers and promoting the system to pubic; and reflecting rural impact assessment to other impact assessment. Researchers: Sang-jin Ma, Dae-shik Park Research Period: 2006. 7 - 2006. 11. E-mail address: msj@krei.re.kr